Physical activity interventions in workplace health promotion: objectives, related outcomes, and consideration of the setting—a scoping review of reviews - Schaller, Andrea; Stassen, Gerrit; Baulig, Lukas; Lange, Martin (Frontiers in Public Health, 2024)
Background The workplace is a recognized setting for promoting health among adults, and physical activity (PA) interventions are an integral part of workplace health promotion (WHP). Objectives The present review of reviews aims to provide an overview of the main objectives and related outcomes addressed in WHP-related PA interventions, as well as the setting-specific aspects considered in the research field. Methods A scoping review of reviews was conducted. Reviews were included if they were peer-reviewed, written in English, and focused on PA interventions conducted in the context of WHP. A literature search was conducted in PubMed, SPORTDiscus, and Web of Science. Reviews were included if they had been published after the year 2000. Information on the following dimensions was extracted: author, region, number of primary studies included, target group(s), PA interventions included, main objective(s), related outcomes, and setting-specific aspects. Results A total of 17 reviews were included. Six reviews aimed at solely identifying the effectiveness of promoting daily PA and reducing sedentary behavior. Eleven reviews showed a combined approach considering physical activity behavior and/or health and job-related outcomes. Outcomes in the primary studies were heterogeneous. None of the reviews had an explicit definition of WHP and setting-specific information was very general and sparse. The reported setting-specific information was referred to the general importance of the workplace setting, the specific importance as an access route to target groups, and implementation aspects. Regarding the additional characteristics of the reviews, the selection of primary studies was restricted to a specific region in 2 of the 17 reviews in advance. Three reviews restricted the target group (sedentary workers, women, desk-based workers), while eleven reviews included working adults in general and, three reviews gave no information about the target group. Eleven intervention approaches of the reviews were behaviorally oriented, two focused solely on environmental interventions, and four reviews can be attributed to a combined approach considering behavioral and environmental interventions. Conclusion For sustainable future developments, the present results indicate a strong need for conceptual consolidation of WHP in the research field of PA interventions. Therefore, both WHP and health-related PA interventions need to take a comprehensive approach comprising behavioral and environmental interventions.